2020
DOI: 10.1177/0272431620919156
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Loneliness in Early Adolescence: The Role of Empathy and Emotional Self-Efficacy

Abstract: Knowledge about the role of empathy, emotional self-efficacy, and loneliness on early adolescents’ depressive symptoms is scarce. The main aims of the study were to investigate the following: (a) the role of empathy and emotional self-efficacy (additive and interactive) on loneliness and depressive symptoms, taking into account gender differences and (b) the possible mediating role of loneliness in the relationship between emotional predictors and depressive symptoms. Three hundred forty-eight Italian early ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 63 publications
2
16
0
2
Order By: Relevance
“…An explanation for these results can be found in the centrality of the emotional dimension for the development of early adolescent girls. As other studies have shown, there can be many difficulties in managing emotions in early adolescence and these usually lead to psychological distress and sometimes depression ( Bandura et al, 2003 ; Grazzani et al, 2015 ; McLaughlin and King, 2015 ; Calandri et al, 2019 , 2021 ). As mentioned above, early adolescent girls use the Internet mainly to maintain and nurture their friendships that are usually characterized by strong emotional charge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An explanation for these results can be found in the centrality of the emotional dimension for the development of early adolescent girls. As other studies have shown, there can be many difficulties in managing emotions in early adolescence and these usually lead to psychological distress and sometimes depression ( Bandura et al, 2003 ; Grazzani et al, 2015 ; McLaughlin and King, 2015 ; Calandri et al, 2019 , 2021 ). As mentioned above, early adolescent girls use the Internet mainly to maintain and nurture their friendships that are usually characterized by strong emotional charge.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, our study focused on emotional self-efficacy that is the perceived ability to regulate and express positive and negative emotions ( Bandura et al, 2003 ). Early adolescence is characterized by great emotional instability and it is a crucial period for the acquisition of the ability of managing and self-regulating emotions ( Grazzani et al, 2015 ; Calandri et al, 2021 ). Research targeting adolescent samples found that girls generally reported lower emotional self-efficacy than boys, especially in managing negative emotions ( Bandura et al, 2003 ; Grazzani et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because self-efficacy is related to stress perception in school settings (Schwarzer and Hallum, 2008 ; Chiu, 2014 ), the development of these skills may depend on the work context: teachers who are in supportive school settings that promote these specific skills amongst its staff and student community are able to better cope with challenging times (Hadar et al, 2020 ). This approach has been fundamental in protecting teachers' and students' psychological well-being (Guidetti et al, 2017 ; Taylor et al, 2017 ; Calandri et al, 2020 ). Based on this literature review (Luszczynska et al, 2009 ; Schönfeld et al, 2016 ), the aim of our study is to analyze the role played by self-efficacy in the relationship between the difficulties in organizing distance learning and teachers' perceived stress.…”
Section: Introductionmentioning
confidence: 99%
“…Emotional self-efficacy reflects a person’s perceived abilities to manage negative emotions (anger, sadness and fear) and to express positive ones (joy, enthusiasm and pride); it plays a pivotal role in the management of different stressors and in influencing depression (Bandura et al, 2003 ; Calandri et al, 2021 ) and well-being (Caprara & Steca, 2005 ). Numerous studies of Caprara et al ( 2006 , 2008 , 2017 ) have highlighted that people’s perceived capability in regulating their positive and negative emotions positively influenced both cognitive and affective SWB.…”
Section: Introductionmentioning
confidence: 99%